Services trade in the United Kingdom and the global economy - Mourougane, Annabelle (OECD Publishing, 2021)
Services play a more important role in trade and employment in the United Kingdom than in most other OECD countries. The UK services sector is supported by an open and transparent trade regime, policies that support competition and innovation, and regulatory transparency that facilitates the creation of new services businesses and start-ups. That said, certain barriers to services trade remain. This report sheds light on the role of services trade in the UK economy, describing recent trends and highlighting future challenges, and explores policy options to support a sustainable recovery from the COVID-19 crisis
Keywords: Trade; Industry and Services; United Kingdom